2003
DOI: 10.1161/01.res.0000069030.30886.8f
|View full text |Cite
|
Sign up to set email alerts
|

Increased Fibronectin Deposition in Embryonic Hearts of Retinol-Binding Protein–Null Mice

Abstract: Abstract-Precise regulation of retinoid levels is critical for normal heart development. Retinol-binding protein (RBP), an extracellular retinol transporter, is strongly secreted by cardiogenic endoderm. This study addresses whether RBP gene ablation affects heart development. Despite exhibiting an Ͼ85% decrease in serum retinol, adult RBP-null mice are viable, breed, and have normal vision when maintained on a vitamin A-sufficient diet. Comparison of RBP-null with wild-type (WT) hearts from embryos at day 9.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 41 publications
(41 reference statements)
0
35
0
Order By: Relevance
“…Apoptosis was assessed with the in situ cell death detection kit (Roche, Mannheim, Germany) according to the manufacturer's instructions as described previously (42)(43)(44).…”
Section: Methodsmentioning
confidence: 99%
“…Apoptosis was assessed with the in situ cell death detection kit (Roche, Mannheim, Germany) according to the manufacturer's instructions as described previously (42)(43)(44).…”
Section: Methodsmentioning
confidence: 99%
“…Within the rodent placenta, RBP is localized on the maternal side in the decidua basalis and the embryonic yolk sac endoderm from 7.0 d post coitum (dpc) (24). Starting from 11.5 dpc, RBP is also expressed in fetal liver (25). We recently demonstrated that maternal RBP does not cross the placenta (26).…”
mentioning
confidence: 99%
“…However, when maintained on a vitamin A-sufficient diet, mice lacking RBP (RBP Ϫ/Ϫ ) yield viable embryos that display only relatively mild and transient cardiac embryonic developmental anomalies (25,29). The unremarkable phenotype of RBP Ϫ/Ϫ embryos reflects the existence of an alternative pathway(s) of vitamin A delivery to the fetus.…”
mentioning
confidence: 99%
“…As in the studies cited, we administered RA to pregnant female rats at high doses at days 8, 9, and 10 post coitum, i.e. in the period when molecules of retinol carriers are present not only in the mother's placental decidua basalis but also in the embryo -from day 7 in the embryonic yolk sac (Sapin et al, 1998) and from day 11.5 post coitum in the liver (Wendler et al, 2003). Therefore, the binding ability of retinol carriers increased at the time of dietary RA administration.…”
Section: Discussionmentioning
confidence: 99%